2014
DOI: 10.1111/apa.12727
|View full text |Cite
|
Sign up to set email alerts
|

Programme to provide Quebec infants with free vitamin D supplements failed to encourage participation or adherence

Abstract: Without educational measures, a free prescription programme for vitamin D failed to encourage participation or adherence. Moreover, participation decreased with time. New strategies, including educational support, need to be developed to increase vitamin D supplementation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…The QPC is created from a linkage of 3 administrative data bases including RAMQ (medical services and prescription claims), MED-ECHO (hospitalizations) and Institut de la Statistique du Québec (birth registry) using the maternal and child provincial health record numbers, date of births and names [10]. As described in more detail in the manuscript concerning term uptake, information such as prescription medications, socioeconomic status (SES), health care provider’s details, hospitalizations, and parental demographics are available in the QPC [8]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The QPC is created from a linkage of 3 administrative data bases including RAMQ (medical services and prescription claims), MED-ECHO (hospitalizations) and Institut de la Statistique du Québec (birth registry) using the maternal and child provincial health record numbers, date of births and names [10]. As described in more detail in the manuscript concerning term uptake, information such as prescription medications, socioeconomic status (SES), health care provider’s details, hospitalizations, and parental demographics are available in the QPC [8]. …”
Section: Methodsmentioning
confidence: 99%
“…Turkey provides vitamin D via prescription [7]. We have recently reported that the province of Quebec has for 20 years utilized a program of free supplements via prescription without a major educational component [8]. Participation (obtaining 1 or more bottles) was limited to only 18% of full term infants during the period 1998–2009.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Free medication alone, however, is not a panacea: a free prescription program in Montreal failed to improve odds of obtaining vitamin D for the infant, with reduced prescription uptake and an increased prevalence of rickets cases over the 4-year study period. 12 WIC serves .50% of infants in the United States, and WIC dieticians are currently an untapped resource for educating, and supporting vitamin D supplementation.…”
Section: -7mentioning
confidence: 99%